Komunitas Moluska pada Berbagai Kondisi Mangrove di Segara Anakan, Cilacap-Jawa Tengah - Nova Mujiono; Nur Rohmatin Isnaningsih (Jurnal Kelautan Tropis, 2022)
The mangrove forest in Segara Anakan lagoon continues to decrease from land conversion or sedimentation. It could have an impact on the diversity of molluscs. This study aims to inventory the diversity and the patterns of mangrove molluscs communities in the Segara Anakan lagoon area. The method used was a 5x5 m2 sample plot in five different mangrove forest cover conditions (dense mangroves, sparse mangroves, planted mangroves, Nipah, and open land). Each category is represented by two stations. The research was inventorying 19 species of molluscs from eight families. The species with the highest number of individuals was Cerithidea weyersi (26.53% of the population). The species with the widest distribution were Littoraria carinifera and Neripteron violaceum. In general, the molluscs communities found from the Segara Anakan Lagoon have moderate diversity, low dominance, and high evenness. The number of individuals and species based on the category of mangrove habitat conditions varies greatly. In dense mangroves (M1) found 119 individuals from 12 species, sparse mangroves (M2) 278 individuals from 15 species, planted mangroves (MT) 129 individuals from 7 species, Nipah (N) 36 individuals from 6 species, and in open land ( LT) collected 29 individuals from 7 species. The data show that sparse mangroves are preferred by molluscs when compared to dense mangroves. Our studies also added 6 species as new records from the Segara Anakan location, thereby increasing the number of molluscs diversity in the area become 61 species.    Hutan mangrove di laguna Segara Anakan terus mengalami penyusutan luas oleh konversi lahan maupun sedimentasi. Hal ini dapat berdampak terhadap keanekaragaman moluska yang hidup di dalamnya. Penelitian ini bertujuan untuk mendata keanekaragaman dan pola komunitas moluska mangrove di kawasan laguna Segara Anakan. Metode yang digunakan adalah dengan menggunakan petak contoh 5x5 m2 pada lima kondisi tutupan hutan mangrove yang berbeda (mangrove padat, mangrove jarang, mangrove ditanam, Nipah, dan lahan terbuka). Masing-masing kategori diwakili oleh dua stasiun. Penelitian berhasil menginventaris 19 spesies moluska anggota dari delapan famili. Spesies dengan jumlah individu terbanyak adalah Cerithidea weyersi (26,53 % dari populasi). Adapun spesies dengan persebaran terluas adalah  Littoraria carinifera dan Neripteron violaceum. Secara umum komunitas moluska yang dijumpai dari Laguna Segara Anakan memiliki keanekaragaman sedang, dominansi rendah, dan kemerataann tinggi. Jumlah individu dan spesies berdasarkan kategori kondisi habitat mangrove sangat bervariasi. Kondisi mangrove padat (M1)dijumpai 119 individu dari 12 spesies, mangrove jarang (M2) 278 individu dari 15 spesies, mangrove ditanam (MT) 129 individu dari 7 spesies, Nipah (N) 36 individu dari 6 spesies, dan pada lahan terbuka (LT) berhasil dikoleksi 29 individu dari 7 spesies. Data kami menunjukkan bahwa mangrove jarang lebih disukai oleh moluska bila dibandingkan dengan mangrove padat. Penelitian kami juga menambahkan 6 spesies sebagai catatan baru dari lokasi Segara Anakan sehingga menambah jumlah keragaman moluska di kawasan tersebut menjadi 61 spesies.